Mechanical properties and Morphology of cement mortar containing nanoparticles - Mohammad Reza Arefi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, the effects of two nano-sized powders (nano-SiO2 and nano-Fe2O3) on the compressive strength, tensile strength and flexural strength of cement mortar were investigated. The results show that the mechanical properties of samples containing 1 and 3 percent nanoparticles are desirable then the ordinary cement mortar. But by increasing nanoparticles up to 5 percent, the mechanical properties reduce severely. However, SEM study about the microstructure of cement mortar containing nanoparticles and ordinary cement mortar showed that nanoparticles reduces the CaOH2 crystals and fills the pores and increases the density of cement mortar.